Assessment of hepatic fibrosis with non-invasive indices in subjects with diabetes before and after liver transplantation - Grancini, Valeria; Cogliati, Irene; Alicandro, Gianfranco; Gaglio, Alessia; Gatti, Stefano; Donato, Maria Francesca; Orsi, Emanuela; Resi, Veronica (Frontiers in Endocrinology, 2024)
Introduction One of the most common complications of cirrhosis is diabetes, which prevalence is strictly related to severity of hepatopathy. Actually, there are no data on the persistence of post-transplant glucose abnormalities and on a potential impact of diabetes on development of fibrosis in the transplanted liver. To this aim, we evaluated liver fibrosis in cirrhotic subjects before and after being transplanted. Methods The study included 111 individuals who had liver transplantation. The assessment was performed before and two years after surgery to investigate a potential impact of the persistence of diabetes on developing de novo fibrosis in the transplanted liver. The degree of fibrosis was assessed using the Fibrosis Index Based on 4 Factors (FIB-4) and the Aspartate to Platelet Ratio Index (APRI). Results At pre-transplant evaluation, 63 out of 111 (56.8%) subjects were diabetic. Diabetic subjects had higher FIB-4 (Geometric mean, 95% confidence interval: 9.74, 8.32-11.41 vs 5.93, 4.71-7.46, P<0.001) and APRI (2.04, 1.69-2.47 vs 1.18, 0.90-1.55, P<0.001) compared to non-diabetic subjects. Two years after transplantation, 39 out of 111 (35.1%) subjects remained with diabetes and continued to show significantly higher FIB-4 (3.14, 2.57-3.82 vs 1.87, 1.55-2.27, P<0.001) and APRI (0.52, 0.39-0.69 vs 0.26, 0.21-0.32, P<0.001) compared to subjects without diabetes. Discussion Thus, persistence of diabetes after surgery is a possible risk factor for an evolution to fibrosis in the transplanted liver, potentially leading to worsened long-term outcomes in this population.